Expectorant Effects of Atractylodes japonica Koidz. ex Kitam Root Extracts on Particulate Matter-Induced Pulmonary Injury in Mice - Junho Lee; Sana Mansoor; Jeongjun Lee; Hunsuk Chung; Young-Sam Kwon; Khawaja Muhammad Imran Bashir; Jae-Suk Choi; Sae-Kwang Ku (Applied Sciences)
This study investigated the growing environmental concern of particulate matter (PM)-induced pulmonary injury and explored novel preventive strategies. In particular, it evaluated the protective effects of Atractylodes japonica Koidz. ex. Kitam root extract (AJ), which is known for its anti-inflammatory and antioxidant properties, against PM2.5-induced subacute pulmonary injuries in Balb/c mice. The experimental design involved administering AJ at a concentration from 400 to 100 mg/kg over a ten-day period, with comparisons made to the mucolytic agent ambroxol hydrochloride (AX). The results revealed that AJ significantly alleviated PM2.5-induced pulmonary injuries, mucus overproduction, and respiratory acidosis in a dose-dependent manner. Notably, body surface redness was reduced by up to 55% at a concentration of 100 mg/kg compared to the control. These effects were evidenced by reduced mRNA expression of the mucus-associated genes MUC5B and MUC5AC and increased concentrations of substance P (up to 475%) and acetylcholine (up to 355%) in the lungs at 400 mg/kg, compared to the intact vehicle control. Particularly, the 400 mg/kg dose of AJ demonstrated comparable effectiveness to AX, highlighting its potent mucolytic and expectorant activities. The results of this study highlight the fact that AJ could act as a promising alternative for respiratory protection, with potential applications as a functional food ingredient. This study substantiates AJ’s role in enhancing respiratory health, emphasizing its capacity as a candidate for further development into therapeutic agents against toxic environmental exposure.